Homophobic bullying at schools: a systematic review of research, prevalence, school-related predictors and consequences (2020)
Recently, research on homophobic bullying has increased. School is a relevant environment in which many bullying experiences take place. This study provides a systematic literature review that examines homophobic bullying at schools by collecting information about its prevalence, school-related predictors and consequences. We considered documents that focused on the study of homophobic bullying in the school context, and provided empirical information on the prevalence, frequency of homophobic bullying or the analysis of some school-related predictor factors or consequences. Ninety documents met the criteria and were, therefore, reviewed. Most studies used samples of adolescents. Their design was based on quantitative methodologies, and they mostly focused on the prevalence and school-related protective and risk factors, such as peer group and social support, followed by school belonging. Some consequences of homophobic bullying are negative academic outcomes, truancy and school belonging. The findings from these studies also provide information about useful strategies, as well as perceived barriers and facilitators. This review may better guide prevention in the education field.